2017
DOI: 10.1016/j.jtho.2016.11.542
|View full text |Cite
|
Sign up to set email alerts
|

P1.01-018 Tobacco Use and Perceptions about Cessation Training among Health Professions Students: Estimates by Countries and WHO Regions

Abstract: Conclusion: There is a dramatic shift of lung cancer toward young peoples in prisons. However, presentation, management and prognosis are similar in prisoners compared to controls. These finding should justify a specific screening policy in that high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…A total of 44% of the HPS reported no formal training in tobacco cessation in the curriculum. This finding is in accordance with several studies confirming that the lack of enough formal training is a widespread problem [33, 3739]. The inclusion of tobacco cessation in the curriculum of the medical schools in low-income countries is faced with multiple barriers, such as lack of available teaching time, staff and financial resources, limited knowledge of the teachers in this field, no plans and organizational problems such as inflexibility of medical curricula to introduce new topics [26, 40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A total of 44% of the HPS reported no formal training in tobacco cessation in the curriculum. This finding is in accordance with several studies confirming that the lack of enough formal training is a widespread problem [33, 3739]. The inclusion of tobacco cessation in the curriculum of the medical schools in low-income countries is faced with multiple barriers, such as lack of available teaching time, staff and financial resources, limited knowledge of the teachers in this field, no plans and organizational problems such as inflexibility of medical curricula to introduce new topics [26, 40].…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study showed a lower percentage of students confirmed a positive perception of their role model status in Toombak cessation than a recent study by Sreeramareddy [33], in which 70% of the students globally agreed that health professionals are role models in tobacco cessation to their patients and public. In addition, previous studies in Sudan showed that between 62–75% of HPS had a positive perception of being a role model to their patients and public in tobacco cessation [27].…”
Section: Discussioncontrasting
confidence: 72%